A ascensão do mercado geek no Brasil - Silva, Nathan Gabriel Reatti da (2022)
Pop culture has become more popular in the entertainment industry, mainly because of movies. The broader and less stereotypical term geek has replaced the nerd label, originally used to denigrate antisocial youth. This has led many individuals to associate themselves with this way of life. The main objective of this research is to understand the items related to pop culture that the geek public buys the most. Among pop culture consumers in São Paulo and region, a questionnaire was applied to carry out field research with quantitative methodology, reaching a total of 38 participants; Data processing was done by interpreting the results and contrasting them with the opinions of many theorists who study the phenomena that involve the geek public in the business and marketing industries. The survey indicates that most participants are between 18 and 25 years old (64%) and that up to two minimum wages make up most of their monthly income (42%). Clothes and shoes top the list of geek products with 31% of the votes, followed by electronic games with 25% of the responses. The Internet (YouTube) and the social network Instagram are the two sources of information most used by customers